1983
DOI: 10.1111/j.1399-3054.1983.tb04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet‐B radiation on the growth and yield of crop plants

Abstract: This paper reviews growth chamber, greenhouse, and field studies on the effects of ultraviolet‐B (UV‐B. between 280 and 320 nm) radiation on agricultural crop plants. Our understanding of the physiological effects of UV‐B radiation comes primarily from growth chamber studies, where UV‐B is artificially supplied via filtered lamps. Both photosystems I and II, as well as carboxylating enzymes, are sensitive to UV‐B radiation. Ultraviolet‐B radiation also affects stomatal resistance, chlorophyll concentration, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
226
1
7

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(239 citation statements)
references
References 33 publications
5
226
1
7
Order By: Relevance
“…However, in leaves irradiated with 10 umol rrr 2 sec" 1 UV-B for 22 hr, lower levels of acidic-type PR-1 accumulated ( Figure 3A), and exposed areas of the leaf showed the classic bronzing and glazing symptoms of UV-B-damaged leaves ( Figure 3B; Teramura, 1983). By contrast, shaded areas of the leaf showed no visible damage ( Figure 3B).…”
Section: Accumulation Of Pr-1 Protein Is Fluence Dependentmentioning
confidence: 98%
“…However, in leaves irradiated with 10 umol rrr 2 sec" 1 UV-B for 22 hr, lower levels of acidic-type PR-1 accumulated ( Figure 3A), and exposed areas of the leaf showed the classic bronzing and glazing symptoms of UV-B-damaged leaves ( Figure 3B; Teramura, 1983). By contrast, shaded areas of the leaf showed no visible damage ( Figure 3B).…”
Section: Accumulation Of Pr-1 Protein Is Fluence Dependentmentioning
confidence: 98%
“…One of the potential consequences of stratospheric ozone depletion, which may result from the continued release of chloro-fluorocarbons, is an increase in the intensity of UV-B radiation at the earth's surface (Teramura, 1983;Frederick and Lubin, 1988). Although mechanisms that may reduce UV-B-induced damage to crop plants have been identified (e.g.…”
Section: ~~ ~ ~ ~mentioning
confidence: 99%
“…Although mechanisms that may reduce UV-B-induced damage to crop plants have been identified (e.g. changes in leaf morphology and epidermal flavonoid content) (Teramura, 1983), these UV-B-induced plant modifications may not be sufficient to prevent decreases in crop yield by enhanced UV-B radiation.…”
Section: ~~ ~ ~ ~mentioning
confidence: 99%
“…Studies have demonstrated the deleterious effects of UV-B (280-315 nm) radiation on photosynthesis, plant growth and development, yield and biomass production (Caldwell, 1971;Teramura 1983;Tevini and Teramura, 1989). These studies used elevated levels of UV-B either as a supplement to natural solar radiation or by artificial UV-B light sources (Caldwell, 1971).…”
Section: Introductionmentioning
confidence: 99%